Covid-19 y deporte en Latinoamérica - de Camilo, Juliana A. O.; Soto-Lagos, Rodrigo (Ariadna Ediciones, 2023)
The chapters that make up the book chart the complexity of the sporting phenomenon, in terms of practices, actors, institutions and conceptual problems considered. Football, Quidditch, practice adventure, social sport, social barrismo, the media, social clubs, government officials, athletes high performance, mental health and gender relations, integrate this complex plot of intersections that makes the study of sport during pandemic.